Exposição da tilápia do Nilo (Oreochromis niloticus) ao triclorfon e a hipercarbia, isolados ou associados - Cardoso, Israel Luz (Universidade Federal de São Carlos, 2021)
Trichlorfon (TCF) is widely used in Brazil and worldwide aquaculture as a compound to control ectoparasites in fish. However, TCF is a pesticide with moderate toxicity in vertebrates and, therefore, its application can be an intensifier of damage on the physiological and biochemical responses in fish already facing problems in environmental quality such as the accumulation of carbon dioxide (CO2). Thus, in this study, an investigation approach was adopted considering the effects of TCF on the health of fish isolated or associated with high [CO2] in the water. Two experiments were developed to investigate such effects: Experiment 1: Nile tilapia exposure to TCF for 96 h was investigated. In this study, we registered behavioral, metabolic and hormonal changes that modified the response patterns of the immune and enzymatic defense systems in the muscle and liver tissues. There was an increase in plasma cortisol and glucose combined with a reduction in acetylcholinesterase activity in muscle and liver tissue after 96 h of exposure to TCF, indicating chemical stress. In response to this harmful situation, we observed changes in the immune system that lead to an increase in the number of leukocytes, thrombocytes, monocyte respiratory activity, lysozyme and leukocytes. In addition, we associate the increased activity of GST in liver tissue as a strategy used by fish to combat the effects of TCF. Therefore, we conclude that the TCF affects the physiological parameters of Nile tilapia, which can generate irreversible effects of recovery of the clinical condition. In experiment 2: Nile tilapia exposure to TCF alone or associated with discharge [CO2] for 48 h was investigated. In this study, we found that the association of experimental conditions intensified the damage to the blood tissue of fish. The reduction in the number of RBC and Ht (%) reveals a deficiency in the transport of O2, offset by the increase in Hb. The reduction in leukocytes and thrombotics indicates less immunological resistance to fight pathogenic diseases or less capacity to recover after damage to the blood tissues. The increase in lysozyme suggests an increase in the action of the nonspecific immune system to fight primary infections in fish. The study also showed that TCF affects the neuromotor cholinergic system of fish by inhibiting acetylcholine (AChE). The antioxidant defense system assessed by the lipoperoxidation marker (LPO) and activity of the enzymes catalase (CAT) and glutathione-S-transferase (GST) in fish were also altered by the action of TCF alone or associated with discharge [CO2]. The increase in OLP suggests that TCF and high [CO2] in water are pro-oxidant factors and, therefore, the positive regulation of CAT and GST activity was to maintain LPO concentrations at levels that are not harmful to liver tissue. Therefore, our study highlights the need to search for new compounds that could replace TCF, having no or few adverse effects on fish species. In addition, considering that high levels of CO2 occur in intensive production, mainly in a water recirculation system, we recommend that the levels of dissolved CO2 should be monitored regularly in the cultivation tanks.
Exposure of Nile tilapia (Oreochromis niloticus) to trichlorfon and hypercarbia, isolated or associated
Keywords: Aquicultura; CO2 da água; Pesticida; Toxicologia; Biomarcadores de efeito; Aquaculture; CO2 from water; Pesticide; Toxicology,; Effect biomarkers; CIENCIAS BIOLOGICAS::FISIOLOGIA